Pelatihan dan Pendampingan Pembuatan Media Pembelajaran Berbasis Teknologi Bagi Guru Sekolah Dasar di Kabupaten Blitar - Ria, Ria Fajrin Rizqy Ana (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2024)
Advances in science and technology have affected the use of teaching aids in schools. Learning in schools is adapted to the development of information technology, resulting in changes and shifts in the paradigm of education, especially the use of learning media. The purpose of this service is to provide knowledge and skills in utilizing information technology to elementary school teachers to support all teaching and learning activities, train elementary school teachers to be able to utilize information technology in every activity, and increase expertise in making presentation materials, learning media and information management. The partners of this service activity are all teachers at SDN Kendalrejo 01, Talun, Blitar. The methods used were lectures, demonstrations, and questions and answers. The results of this activity, namely the implementation of this service activity, are said to have been achieved because most of the teachers who have attended the training activities and succeeded in making an interactive learning media according to the subjects taught at school.